Current research on cigarette toxicity: critical appraisal in view of clinical laboratory - Gyawali, Prajwal; Oguoma, Victor Maduabuchi (International Journal of Research in Medical Sciences, 2017)
Cigarette smoking has been implicated as a potential risk factor for development and progression of chronic obstructive pulmonary disease (COPD) and cardiovascular disease (CVD), including ischemic heart disease. Although, several methods are in existence to measuring cigarette toxicity, evidence regarding adoption of a gold standard technique is still imprecise. In this study, we reviewed articles describing methods of measuring cigarette toxicity in relation to clinical laboratory practice. A critical analysis of the benefits and limitations of each method in relation to low-middle income countries is discussed.